Novel Plasmodium antigens identified via genome-based antibody screen induce protection associated with polyfunctional T cell responses. Issue 1 (December 2017) - Schussek, Sophie; Trieu, Angela; Apte, Simon; Sidney, John; Sette, Alessandro; Doolan, Denise
Abstract The development of vaccines against complex intracellular pathogens, such asPlasmodium spp ., where protection is likely mediated by cellular immune responses, has proven elusive. The availability of whole genome, proteome and transcriptome data has the potential to advance rational vaccine development but yet there are no licensed vaccines against malaria based on antigens identified from genomic data. Here, we show that thePlasmodium yoelii orthologs of fourPlasmodium falciparum proteins identified by an antibody-based genome-wide screening strategy induce a high degree of sterile infection-blocking protection against sporozoite challenge in a stringent rodent malaria model. Protection increased in multi-antigen formulations. Importantly, protection was highly correlated with the induction of multifunctional triple-positive T cells expressing high amounts of IFN-γ, IL-2 and TNF. These data demonstrate that antigens identified by serological screening are targets of multifunctional cellular immune responses that correlate with protection. Our results provide experimental validation for the concept of rational vaccine design from genomic sequence data.